Pan-Genome Analysis of Vibrio cholerae and Vibrio metschnikovii Strains Isolated From Migratory Birds at Dali Nouer Lake in Chifeng, China - Zheng, Lin; Zhu, Ling-Wei; Jing, Jie; Guan, Jia-yao; Lu, Ge-Jin; Xie, Lin-Hong; Ji, Xue; Chu, Dong; Sun, Yang; Chen, Ping; Guo, Xue-Jun (Frontiers in Veterinary Science, 2021)
Migratory birds are recently recognized as Vibrio disease vectors, but may be widespread transporters of Vibrio strains. We isolated Vibrio cholerae (V. cholerae) and Vibrio metschnikovii (V. metschnikovii) strains from migratory bird epidemic samples from 2017 to 2018 and isolated V. metschnikovii from migratory bird feces in 2019 from bird samples taken from the Inner Mongolia autonomous region of China. To investigate the evolution of these two Vibrio species, we sequenced the genomes of 40 V. cholerae strains and 34 V. metschnikovii strains isolated from the bird samples and compared these genomes with reference strain genomes. The pan-genome of all V. cholerae and V. metschnikovii genomes was large, with strains exhibiting considerable individual differences. A total of 2,130 and 1,352 core genes were identified in the V. cholerae and V. metschnikovii genomes, respectively, while dispensable genes accounted for 16,180 and 9,178 of all genes for the two strains, respectively. All V. cholerae strains isolated from the migratory birds that encoded T6SS and hlyA were non-O1/O139 serotypes without the ability to produce CTX. These strains also lacked the ability to produce the TCP fimbriae nor the extracellular matrix protein RbmA and could not metabolize trimetlylamine oxide (TMAO). Thus, these characteristics render them unlikely to be pandemic-inducing strains. However, a V. metschnikovii isolate encoding the complete T6SS system was isolated for the first time. These data provide new molecular insights into the diversity of V. cholerae and V. metschnikovii isolates recovered from migratory birds.